2010
DOI: 10.1037/a0018395
|View full text |Cite
|
Sign up to set email alerts
|

Sufficiency of longitudinal moment of inertia for haptic cylinder length judgments.

Abstract: Many studies invoke moment of inertia (Iii) as necessary and sufficient information to perceive cylinder length via wielding, yet some assert that Iii is neither necessary (weight, m, or static moment, M, are sufficient) nor sufficient for length judgments (m or M is necessary). Mathematical expressions for Iii not involving m or M imply length, so Iii could be sufficient for cylinder length judgments. In 5 experiments (N = 113), only longitudinal Iii (the smallest principal value) informed cylinder length est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 90 publications
3
23
0
Order By: Relevance
“…The single participant who showed a negative correlation between actual and estimated IFD evidently perceived the differences present but applied a reversed scaling relationship. Similar outcomes, particularly with novel perceptual tasks, have been reported elsewhere (Cabe, 2010(Cabe, , 2011Cabe & Hofman, 2012;Withagen & Caljouw, 2011), all notably in haptic perceptual studies. In all those instances, participants apparently were sensitive to relevant information but applied an inverse scaling relationship (see also the discussion of similar outcomes in Experiment 1B).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The single participant who showed a negative correlation between actual and estimated IFD evidently perceived the differences present but applied a reversed scaling relationship. Similar outcomes, particularly with novel perceptual tasks, have been reported elsewhere (Cabe, 2010(Cabe, , 2011Cabe & Hofman, 2012;Withagen & Caljouw, 2011), all notably in haptic perceptual studies. In all those instances, participants apparently were sensitive to relevant information but applied an inverse scaling relationship (see also the discussion of similar outcomes in Experiment 1B).…”
Section: Discussionsupporting
confidence: 62%
“…Whether the particular pattern of array properties available in Experiment 1A is unique to the perceptual judgment tested is an open question. Cabe (2010), for example, showed that a subset of physical-mechanical information was sufficient to support length judgments of cylinders rolled by hand, where previous analyses had suggested that additional information was required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adopting this conjecture accommodates the data (for elaboration, see [21,22,35]). Whether this spinor-supplemented inertia tensor theory is the right theory and whether any theory of dynamic touching limited to second moment conceptions (that is, ignoring zeroth and first moment conceptions) is sufficient are open issues awaiting more research [30,36,37].…”
Section: Selectively Attending To Wholes (Exteroception) and To Partsmentioning
confidence: 99%